PENGARUH KOMITMEN ORGANISASIONAL DAN KEPUASAN KERJA TERHADAP KEINGINAN BERPINDAH (TURNOVER INTENTION) KARYAWAN PT. FIF CABANG MATARAM - Rosyia Wardani (Valid: Jurnal Ilmiah, 2016)
The title of this research is "The effect of organizational commitment and job satisfaction on turnover intentions at PT. FIF Branch Mataram employees". Aims (1) To determine significant simultant effect of Organizational Commitment and job satisfaction on turnover intention of employees at PT FIF Branch Mataram; (2) to determine the significant partial effect of Organizational Commitment and job satisfaction on turnover intention of employees at PT FIF Branch Mataram; (3) to determine dominant effect among Organizational commitment and job satisfaction on turnover intention of employees at PT FIF Branch Mataram. In accordance with the purpose of research, the type of research used in this research is causal. The population is all of the employees about 122 peoples. Determination of the respondents in this study carried out on all members of the population, it has been called a census. To collect data in this research used questionnaires. To determine the responses of respondents to variables assessed, used Likert Scale analysis with the 5 scales answered point. The results showed that: (1) There is a significant simultant effect of organizational commitment and job satisfaction on turnover intentions of employees at PT. FIF Branch Mataram, (2) There is a significant partial effect of organizational commitment and job satisfaction on turnover intentions of employees at PT. FIF Branch Mataram, (3) Job satisfaction has a dominant effect on turnover intentions of employees at PT. FIF Branch Mataram